CHALLENGES AND POTENTIAL INTERVENTIONS IN ARTISANAL FISH PRODUCTION ALONG OGUN RIVER BASIN - Adeosun, O.M.; Adeosun, F.I.; Soyoye, V. O.; Ajiboye, E. O.; Fadeyi, P. B. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study profiled the challenges and potential interventions in artisanal fish production along Ogun River basin. Two stage sampling technique was employed to select 120 artisanal fishers. Data were collected with the aid of structured and validated interview guide . Data were analyzed using descriptive and inferential statistics. The result showed that majority of the artisanal fishers were male and married (59.1%) with a mean household size of 8.5. Results also showed that the age range of 41-50 and 21-30 had the highest percentage of 40% and 20.8% respectively. The results further revealed that 34.45% and 34.1% of the respondents had primary education and no formal education respectively. Oreochromis niloticus has a higher percentage of abundance and distribution in the study area 58.3%. The major constraints among fishers is decline in fish population, it revealed that 90.8% of the respondents had no access to interventions or supports while 9.2% of the respondents had access to interventions or supports. Results on the distance covered on fishing trips revealed that <5km had a high percentage of 87.5%, while 5km- 10km had a percentage of 12.5%. Also, the distance covered of each fisher man/woman to operation site and also how near and far the operation site is to their landing site or homes. Additionally, it revealed that the full-time and part-time fishers had a percentage of 70.8% and 29.1% respectively of the total population. This explains that most of the fishers are fully involved in fishing as their main occupation. Based on the findings of this study, it was revealed that artisanal fishers along the Ogun River Basin continue to experience significant challenges that affect their operations, even in the presence of measurable yield and productivity. These challenges highlight critical areas where strategic and context-specific interventions are required to enhance artisanal fish production, strengthen livelihoods, and promote the sustainable management of fisheries resources in the study area.